Authoring Tool for Location-Aware Experiences - Alconada Verzini, Federico M. (2015)
In this paper, we present an approach to create location-aware experiences. We use the concept of separation of concerns to represent the content layer and the location layer. This separation allows reusing the layers independently one of each other. The focus of this paper is to provide an end-user tool to create location-aware applications in-situ. By using our tool, the location-aware experiences can be defined in both indoor and outdoor spaces. We present an example of how our tool is used and we describe some discussion points that have occurred to us while defining a tool with these characteristics.